Comparison of the initial surgical experience with robotic and laparoscopic myomectomy. Issue 2 (3rd October 2013) - Pluchino, Nicola; Litta, Piero; Freschi, Letizia; Russo, Marinella; Simi, Giovanna; Santoro, Anna N.; Angioni, Stefano; Gadducci, Angiolo; Cela, Vito
Abstract Objective To compare the initial surgical outcomes of robotic and laparoscopic myomectomy in patients with symptomatic uterine myomas. Study Design Retrospective chart review of 86 patients undergoing robotic (RM) (n = 43) or laparoscopic (LM) (n = 43) myomectomy. Data included fibroid characteristics (number, weight, location) layers of uterine reconstruction, operating time, blood loss, complications, and postoperative hospital stay. Results No significant differences were noted between RM and LM for fibroid number and weight and mean operating time, although the number of patients receiving at least a double‐layer uterine reconstruction was higher in RM than LM. Blood loss was higher after LM, while no differences resulted in hospital stay. Conclusion RM may have some additional advantages compared with LM in terms of bleeding and uterine suturing without compromising operation duration, at least when surgeons were at the beginning of their experience of endoscopic treatment of symptomatic uterine myomas. Copyright © 2013 John Wiley & Sons, Ltd.